A Cross-Knotted Suture Basket Technique for Large Nonmagnetic Intraocular Foreign Body Removal - Jian Cao; Baihua Chen; Yun Li (Journal of Ophthalmology)
Purpose. To report a novel technique of cross-knotted suture basket and to test its effectiveness in large nonmagnetic intraocular foreign body (IOFB) removal. Methods. A 7/0 Vicryl suture was cut in half and cross-knotted, and four ends were introduced into a 23G needle to form a basket. Pig eyes were used to set up the IOFB model, and the effectiveness of the suture basket in the removal of large nonmagnetic intraocular foreign bodies was tested. Results. Several modifications can be made to adapt to different situations. For the materials (stone, metal, glass, and wood) and shapes (irregular, spherical, and rectangle) of large IOFB tested, the cross-knotted suture basket successfully removed all kinds of IOFBs. Conclusion. The suture basket technique provides an accessible, safe, and effective alternative in large nonmagnetic IOFB removal. It can be adapted and interchangedand also worth’s further clinical investigations.